Cholesterol granuloma in the neck – a case of vocal fold paralysis - Azevedo, Sara Raquel (2021)
Introduction: The aim of this study was to report a case of cholesterol granuloma in the neck with vocal cord paralysis. Case report: A 75-year-old male patient with recent onset of hoarseness complaints followed on Otorhinolaryngology appointment. Objective examination with flexible nasopharyngolaryngoscopy showed a paralysis of the left vocal cord. Neck CT scan showed a solid nodular lesion in the left vascular space of the neck. Surgical excision was performed and histological diagnosis showed a thymic granuloma of cholesterol. Discussion: Cholesterol granuloma develops in response to cholesterol crystals and foreign body giantcells. It is described as a benign condition affecting the middle ear mostly. It has already been described in other organs but is rarely described affecting the neck. Surgical excision and histological examination are essential to treatment and diagnosis.